Kelayakan Investasi Perluasan Pabrik Penggilingan Plastik PD XYZ - Hartiwi Prabowo (Bina Nusantara University, 2012)
PD. PENGGILINGAN PLASTIK XYZ is a company engaged in the manufacturing industry. Recently, demands for products are increasing and the company finds it difficult to meet the demands. Therefore, the company wants to expand the factory to increase output of the products. The purpose of this study is to determine whether the expansion of businesses that want to run is well-worth in terms of financial and nonfinancial aspects. The research method used is descriptive qualitative and quantitative methods. Qualitative descriptive analysis method is used to analyze the legal, technical/operations, markets and marketing, management/organizational, economic, social and environmental impacts. Quantitative descriptive analysis method is used to analyze the financial aspects, the market and marketing. The results of the feasibility study of the factory expansion from the financial aspect refer to an optimistic scenario assumptions and moderate, and worthy to do. Similarly, the non-financial aspects, all aspects point out that the expansion of the factory is feasible to do. By this, the company is expected to maintain a stable supply of raw materials, because, if the supply of raw materials is interrupeted, the operation cannot run.